The kingdom of the prolyl-isomerase Pin1: The structural and functional convergence and divergence of Pin1 - Lee, Yew Mun; Teoh, Deryn En-Jie; Yeung, Kay; Liou, Yih-Cherng (Frontiers in Cell and Developmental Biology, 2022)
More than 20 years since its discovery, our understanding of Pin1 function in various diseases continues to improve. Pin1 plays a crucial role in pathogenesis and has been implicated in metabolic disorders, cardiovascular diseases, inflammatory diseases, viral infection, cancer and neurodegenerative diseases such as Alzheimer’s, Parkinson’s and Huntington’s disease. In particular, the role of Pin1 in neurodegenerative diseases and cancer has been extensively studied. Our understanding of Pin1 in cancer also led to the development of cancer therapeutic drugs targeting Pin1, with some currently in clinical trial phases. However, identifying a Pin1-specific drug with good cancer therapeutic effect remains elusive, thus leading to the continued efforts in Pin1 research. The importance of Pin1 is highlighted by the presence of Pin1 orthologs across various species: from vertebrates to invertebrates and Kingdom Animalia to Plantae. Among these Pin1 orthologs, their sequence and structural similarity demonstrate the presence of conservation. Moreover, their similar functionality between species further highlights the conservancy of Pin1. As researchers continue to unlock the mysteries of Pin1 in various diseases, using different Pin1 models might shed light on how to better target Pin1 for disease therapeutics. This review aims to highlight the various Pin1 orthologs in numerous species and their divergent functional roles. We will examine their sequence and structural similarities and discuss their functional similarities and uniqueness to demonstrate the interconnectivity of Pin1 orthologs in multiple diseases.